Causal Connection of Macro and Micro Systems in Function of Spatial - Temporal Resonance - Kuka, Miroslav; Panovski, Miroslav (European Journal of Applied Sciences, 2023)
By discovering natural laws, one learns about relatively stable causal connections between objects and phenomena. Causal relations can be functionally connected (when one phenomenon without exception causes another - natural phenomena) and stochastically (connection of phenomena with exceptions - social phenomena). Phenomena in nature are perceived and occurred according to valid laws for all people. However, there are phenomena that are not perceived by all people, they do not have valid laws for everyone, but in certain causally symbolic interpretations, they are valid for certain individuals, who perceive the phenomena and then causally connect them with some of their initiated actions from the past or present, which the outcome they expect. Therefore, these phenomena occur in nature (society), and as a spontaneous response, i.e. anticipating the outcome of actions started but not completed by a certain individual. We cannot mathematically describe the above-mentioned causal relationships, but we interpret them with the aim of anticipating the outcome of the initiated but unfinished actions of individuals. For now, we can believe or not believe in these phenomena and their causally symbolic connections, as well as in theological dogmas, because we are not at the stage of cognitive development to interpret and prove them indisputably. The spatial-temporal synchronicity between natural phenomena that can be scientifically explained and phenomena that have no explanation, we called "The Kuka - Panovski Resonance". In that resonance, i.e. natural phenomena with their causally symbolic interpretations, time is extrasensory, infinite and independent of space, and space is sensory and dependent on time. In addition, we have to distinguish time, which we measure through space and movement, from infinite time, i.e., constant present produced by our consciousness. The causal connection of phenomena (action / reaction) in nature, with individual actions which outcome they anticipate, is most often judged "ex post facto", i.e. when the outcome of the initiated action has already occurred. However, we start from the premise that in the "The Kuka - Panovski Resonance", as well as in the whole of nature, all phenomena and outcomes (actions and reactions) are mutually-causally connected. From this causal connection, we hypothetically assume that spontaneous phenomena in nature (macro, higher system) provide answers in advance, i.e., they anticipate the outcome of the initiated actions of each human (micro, lower system), which is the part of that same nature. It is believed that the visible world is a storehouse of images and signs, which first need to be perceived and then revealed their hidden meaning through the causal symbolic method. The scientist or the artist act in the capacity of translator of that universal analogy. In this work, we shall describe methodologically the phenomena that, according to our knowledge, are in stable causal relationships, which official science does not accept yet. By understanding these phenomena in their stable causal relationships, modern science would take a big step in its future development.